A quality enhanced preprocessing method for mammogram ROI extraction - R. Thamizhvani, T; Babu, Bincy; Josephin Arockia Dhivya, A; J. Hemalatha, R; Elsa Joseph, Josline; Keerthana, A (International Journal of Engineering and Technology, 2018)
Early detection of breast cancer is necessary because it is considered as one of the most common reason of cancer death among women. Nowadays, the basic screening test for detection of breast cancer is Mammography which con-sists of various artifacts. These artifacts leads to wrong results in detection of breast cancer. Therefore, Computer Aided Diagnosis (CAD) system mainly focus in removal of artifacts and mammogram quality enhancement. By this procedure, exact Region of Interest (ROI) can be obtained. This is a challenging procedure because detection of pecto-ral muscle and cancer region is difficult. Here a comparative study of different preprocessing and enhancement tech-niques are done by testing proposed system on mammogram mini-MIAS database. Result obtained shows that sug-gested system is efficient for CAD system.Â Â